Yupi PENGARUH VARIASI TEMPERATUR DAN KATALIS ZEOLIT TERHADAP KARAKTERISTIK BIO-OIL DARI PIROLISIS LIMBAH LDPE, BAN, BAMBU - Majedi, Farid; Eka Indriana, Yupi; Puspitasari, Indah (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2025)
The problem of dwindling fossil fuels, waste in Winongo landfill, Madiun which is over capacity. An alternative energy (renewable) is needed, which can be produced from waste as an alternative fuel to replace fossil fuels, one of which is pyrolysis. Pyrolysis is the process of thermochemical decomposition of organic materials through heating without or little oxygen to produce gaseous, liquid (tar), and charcoal products. Natural zeolite is used as a catalyst in the pyrolysis process to convert short hydrocarbon chains into longer hydrocarbon chains. The pyrolysis process uses a pyrolysis device with a rotary kiln model with electric heater heating. This research process uses a total raw material weighing 500 grams including 50% LDPE plastic waste, 25% used tires, and 25% used bamboo with the variables used in this study are temperature variations of 250°C, 300°C, 400°C, 500°C, and 600°C and the addition of 2 natural zeolite catalyst baffles weighing 83.3 grams in each baffle, with a process of 3 hours. Bio-oil volume data was taken every 3 minutes, density and calorific value were studied when the pyrolysis process was complete. The test results showed the highest volume of bio-oil (tar) at 400°C was 261 ml, the lowest density at 600°C was 0.798 g/ml, and the highest calorific value at 500°C was 54,233 Cal/gr.